Behavior of Laminated Reinforced Concrete Curved Beam with Changing Concrete Properties - Hesham A. Numan; Waleed A. Waryosh; Shaima Sabri Ali (Civil Engineering Journal, 2019)
Strengthening and upgrading the performance reinforced concrete curved structures for functional purpose as well as for conversation of architectural aesthetic aspect is the main concern for engineers. In the present study, four full-scale experimental Curved Reinforced Concrete (CRC) beams conducted. The cross-section of all CRC beams was T-section. The parametric studies are carried out to investigate the effect of time of casting segmental layers (web and flange) and the compressive strength of concrete on the structural behavior of such structures. Three values of compressive strength of concrete used in this study, these are (25, 50, 75 MPa). The control specimen casting as one unit with the compressive strength of concrete was 25 MPa. The present outcomes showed that the increase in the compressive strength of concrete up to 75 MPa of the flange zone plays a significant role in raising the ultimate capacity by 22.86% and reducing the deflection by 61.43% in the quarter span as compared with control specimen. Additionally, the trend and distribution of cracks, mode of failure, and strain response of CRC specimens are briefly discussed in this study.